2018
DOI: 10.7596/taksad.v7i3.1628
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul Bahçelerinde Davranış Haritaları Bağlamında Mekânsal ve İşlevsel Bir Analiz: Trabzon Örneği / A Spatial Functional Analysis in the Context of Behavioral Maps in Primary School Grounds: Case of Trabzon

Abstract: <p><strong>ABSTRACT</strong></p><p>Primary school gardens are areas where children spend extracurricular time. The gardens are influential on children's physical, social and academic development. School gardens should be designed according to the needs of the students from different age groups. During the design process of school gardens, the standards defined in the context of hierarchical space fiction are ignored. This leads to spatial inadequacies in school gardens and also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…When studies on the threshold space are examined, it is observed that several common techniques are utilized, the most prevalent of which are the observation method (Danilina & Privezentseva, 2020;Akartuna, 2017;Şevik, 2018) and the processing of observation data on maps (Eltan et al, 2015;Akartuna, 2017;Şevik, 2018). The method of processing user observation data on the map is called the "behavior mapping technique" (Eltan et al, 2016;Akartuna, 2017;Sevik, 2018;Barker, 1968;Ittelson, Rivlin, & Prohansky ,1970;Goličnik Marušić, 2010;Guinther et al, 2014;Al-Maimani et al, 2014;Mandel, 2016;Karadeniz et al, 2018;Ozbil et al, 2018;Gharib, 2019;Onojeghuo et al, 2019;Istrate et al, 2020;Wang & Wu, 2020;Cosco et al, 2010;McQuilkin, 2016;Van der Spek et al, 2009;Valkenet et al, 2022;Milke et al, 2009;Cox et al, 2018;Arsan & Kepez, 2017;Liao et al 2022). Behavior mapping technique was first developed at the end of the 1960s, by environmental and behavioral researchers such as Barker (1968) and Ittelson, Rivlin, & Prohansky (1970).…”
Section: On-site Observation and Behavior Mapping Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…When studies on the threshold space are examined, it is observed that several common techniques are utilized, the most prevalent of which are the observation method (Danilina & Privezentseva, 2020;Akartuna, 2017;Şevik, 2018) and the processing of observation data on maps (Eltan et al, 2015;Akartuna, 2017;Şevik, 2018). The method of processing user observation data on the map is called the "behavior mapping technique" (Eltan et al, 2016;Akartuna, 2017;Sevik, 2018;Barker, 1968;Ittelson, Rivlin, & Prohansky ,1970;Goličnik Marušić, 2010;Guinther et al, 2014;Al-Maimani et al, 2014;Mandel, 2016;Karadeniz et al, 2018;Ozbil et al, 2018;Gharib, 2019;Onojeghuo et al, 2019;Istrate et al, 2020;Wang & Wu, 2020;Cosco et al, 2010;McQuilkin, 2016;Van der Spek et al, 2009;Valkenet et al, 2022;Milke et al, 2009;Cox et al, 2018;Arsan & Kepez, 2017;Liao et al 2022). Behavior mapping technique was first developed at the end of the 1960s, by environmental and behavioral researchers such as Barker (1968) and Ittelson, Rivlin, & Prohansky (1970).…”
Section: On-site Observation and Behavior Mapping Techniquementioning
confidence: 99%
“…The study was conducted in one university library. Karadeniz et al, 2018. Creating behavior maps for primary school students' use of school gardens in 5 primary schools selected from different regions in the city of Trabzon and conducting spatial-functional analysis.…”
Section: •Location •Activitymentioning
confidence: 99%
See 3 more Smart Citations